Clinical profile and outcome of dengue fever in a paediatric tertiary care centre - Moinuddin, Md khaja; Sahana Devadas, Sahana Devadas (International Journal of Contemporary Pediatrics, 2017)
Background: A study of different presentation and outcome of dengue fever in tertiary care centre. Methods: the observational cross sectional study was carried out from June to October 2016 in Bowring and Lady Curzon hospital attached to Bangalore Medical College and Research Institute. Included patients from 1 to 18 years of age who presented with febrile illness. WHO classification and definitions were used to classify disease as dengue fever (DF), dengue haemorrhagic fever (DHF) and dengue shock syndrome (DSS). Clinically, haematological and biochemical findings were recorded till discharge. Results: during study period,142 patients presented with typical features of dengue fever, male being 86 (60%) and female being 56 (40%). Among 142 cases 64 cases were probable dengue, 50 cases were dengue with warning signs and 28 cases were had severe dengue. Fever (100%) was the most common clinical presentation followed by vomiting (70%), body ache (43%), abdominal pain (23%), headache (12%) and rashes (5%). Laboratory findings included thrombocytopenia, leucopenia and elevated liver enzymes. 126 (88%) cases were discharged in clinical stable conditions, (8%) were died during course of treatment and 8 cases left against medical advice. Conclusions: fever with vomiting and thrombocytopenia were most common presentation of dengue fever, appropriate clinical diagnosis and management is relatively simple, inexpensive and very effective in saving lives as long as long correct and timely interventions instituted.